PENGARUH FLUKS B203 DAN BEBERAPA PARAMETER PEMROSESAN PADA BENTUKAN SUPERKONDUKTOR BPSCCO-2223 - Gede Suharta, Wayan
AbstraCT: An experiment has been carried out for studying the effects of B2O3 flux on the formation of the 2223 phase of BSCCO superconductor by means of solid state reaction with Pb doping. For this study the flux contenct is varied between 0.00 and 0.01 in molar ratios, while the sintering temperature and sintering time are varied respectively from 825°C to 856°C and from 60 to 120 hours. In this connection, an additional experiment has also been conducted to investigate the effect of cooling rate on the samples. Measurements of XRD spectra and p-T curves on tha samples reveal that 0.05 molar ratio of B2O3 and sintering temperature of 850°C appear to provide the optimal condition for tthe growth of the 2223 phase and the enhancement of its volume fraction. Improvement of grain quality of the sample also show with additional sintering time. The result of XRD spectra of the sample sintered for 160 hours, better than samples sintered for short time. Furthermore, the recorded SEM picture and EDAX data also showed different grain qualitiesof sample is treated by furnace cooling and slow cooling. Further experiments are needed, however, for more conclusive results.